ANALISIS DANA DESA – IMPLEMENTASI KEBIJAKAN DANA DESA PADA KAMPUNG SUKAN KABUPATEN BERAU - RAHMAWATI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2022)
Accountability for managing village funds begins with planning, implementation, administration, reporting, and accountability in Sukan Village, Berau Regency. Based on this research, it aims to analyze how the accountability of village fund management is in Sukan Village, Berau Regency. Where in this research was carried out at the Office of the Head of Sukan Village with the Village Head, Village Secretary, and Village Treasurer. Based on the results of the study, it is known that the level of accountability for the implementation of village fund management in Sukan Village at the planning stage has been carried out in a transparent and participatory manner, namely by involving the community in every decision making and has also shown transparent management. Likewise at the implementation stage and accountability has been carried out in an accountable and transparent manner to the public. So that the accountability of village fund management can be relied upon.